Comparison of mortality in higher ages for the countries of Visegrad Group with focus on life expectancy changes - Szewczyk, Paulina Anna; Miskolczi, Martina; Hon, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
Mortality is an important demographic component that is significant in everyone’s life and brings important information about the population’s health. This master’s thesis aims to investigate and compare mortality rates with a specific focus on changes in life expectancy of the Visegrad Group (Czechia, Hungary, Poland, and Slovakia). The Visegrad Group countries share a common geographic location in Central Europe, and they have experienced similar socio-economic and demographical transformations. This paper will focus on analyzing mortality patterns in higher ages groups. Examining historical trends in mortality rates and life expectancy provides insight about elderly’s people health and well-being. Theoretical part of the thesis explains definitions and used terms as well as different mortality measures. There is also a description of the current situation in the Visegrad Group countries with the changes happening due to the ageing population. The research methodology involves data from Eurostat. Analysis is conducted by calculating mortality indicators as crude death rate, age-specific mortality rate but also differences in life expectancy over time. Results are visualized on charts and tables. For a deeper understanding of the relations of the life expectancy, spatial analysis is performed. Findings of this study show that migration is changing in a non-linear way and there are similar trends across countries. Mortality rate is sensitive for events that are influencing population size. Hungary over the years had the highest mortality rate which can be associated with high ageing rate. On the contrary Slovakia has the lowest mortality rate due to its younger population. Additionally, life expectancy is increasing in all countries over time. The most dynamic growth is observed in Czechia. Performed spatial autocorrelation analysis shows presence of regional clustering and existing dependencies in life expectancy values.
Results presented on the maps indicate exact regions that are correlated with each other.
Vedoucí práce: Martina Miskolczi
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses